Fiscal Effectiveness and Efficiency in Driving Regional Economic Development: Evidence from Banten Province - Budi Prajogo; Farhat Abas (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study examines the effect of expenditure effectiveness and efficiency on regional economic development in Banten Province. The research addresses a key issue in public financial management concerning how regional budgets can be optimally allocated and utilized to maximize development outcomes. A quantitative approach is applied using multiple linear regression based on regional budget data and economic indicators from official government sources for the period 2015–2023. The regression results indicate that expenditure effectiveness positively and significantly affects economic development (β = 0.052; p = 0.013), while expenditure efficiency also demonstrates a positive and significant influence (β = 0.038; p = 0.020). Simultaneously, both variables significantly explain regional economic growth (F = 19.72; p = 0.002), with a coefficient of determination (R²) of 0.842, indicating strong explanatory power. These findings imply that improving budget absorption, strengthening implementation efficiency, and adopting evidence-based planning are essential to enhance regional development performance. The study recommends reinforcing value-for-money principles and accelerating financial digitalization to improve public expenditure quality.